SIKAP PETANI PADI TERHADAP INOVASI PUPUK ORGANIK NITROBAKTER DI KECAMATAN JATEN KABUPATEN KARANGANYAR - Sanubari, Hafidh Tegar; Lestari, Eny; Utami, Bekti Wahyu (Universitas Sebelas Maret, 2026)
This study aimed to analyze rice farmers’ attitudes toward the innovation of Nitrobacter organic fertilizer in Jaten Subdistrict, Karanganyar Regency, and to identify factors associated with attitude formation. A quantitative survey method was employed involving 45 rice farmers selected from villages representing different levels of innovation adoption. Primary data were collected through structured questionnaires using a five-point Likert scale and analyzed using descriptive statistics and Spearman Rank Correlation. The results showed that farmers generally had positive attitudes toward the innovation, particularly regarding relative advantage, compatibility, trialability, and observability. However, moderate hesitation remained concerning the technical complexity of application. Non-formal education, farming experience, extension workers’ roles, internet media use, and socio-cultural factors were significantly associated with farmers’ attitudes (p < 0.05). Among these variables, socio-cultural factors had the strongest relationship. These findings indicate that increasing adoption of Nitrobacter organic fertilizer requires participatory extension programs, field demonstrations, digital information support, and locally adaptive communication strategies.